Influence of Multiphase Flexible Timber Frame House Construction on Housing Affordability. (2015) - Milwicz, Roman; Nowotarski, Piotr
Abstract: Purchase of a large and expensive house becomes more distant vision for most people due to high initial cost, the size estimation difficulties, oversizing effects in higher mortgage and cost of maintenance. Recognizing those problems, a flexible multi-step construction of a house frame structure has been proposed, in order to reduce costs and adapt to the current needs of the end users. Proposed solutions are based on life cycle cost (LCC) analyses, monthly maintenance cost and flexible methodology. Paper presents comparative analysis of brick and timber structure frame house.